Athletes` narratives of caring coaches who made a difference - Gano-Overway, L. A. (Sports Coaching Review, 2023)
The purpose of this study was to explore athletes` experiences with caring coaches who had influenced their lives. The researcher interviewed college students who were former high school athletes about their experiences with caring coaches using a narrative inquiry approach. Eight participants told stories about their high school coaches. Working with the athletes, the researcher created narratives that described the thoughts, feelings, and behaviours surrounding the relational experience with the coach associated with positive development through sport. While each narrative was unique to its personal and social context, the researcher, using a thematic narrative approach, shared four approaches to caring connected to theoretical and empirical work on caring. These approaches to care included supporting and encouraging athletes, creating community and connection, balancing care with other aspects of team culture, and engaging in tough love. Findings provide further insight into how coaches might establish caring practices to further holistic athlete development.